White dwarf planets - Bonsor Amy; Veras Dimitri; Villaver Eva; Mustill Alexander J.; Wyatt Mark C. (EPJ Web of Conferences, 2013)
The recognition that planets may survive the late stages of stellar evolution, and the prospects for finding them around White Dwarfs, are growing. We discuss two aspects governing planetary survival through stellar evolution to the White Dwarf stage. First we discuss the case of a single planet, and its survival under the effects of stellar mass loss, radius expansion, and tidal orbital decay as the star evolves along the Asymptotic Giant Branch. We show that, for stars initially of 1 − 5 M⊙, any planets within about 1 − 5 AU will be engulfed, this distance depending on the stellar and planet masses and the planet's eccentricity. Planets engulfed by the star's envelope are unlikely to survive. Hence, planets surviving the Asymptotic Giant Branch phase will probably be found beyond ∼ 2 AU for a 1  M⊙ progenitor and ∼ 10 AU for a 5 M⊙ progenitor. We then discuss the evolution of two-planet systems around evolving stars. As stars lose mass, planet–planet interactions become stronger, and many systems stable on the Main Sequence become destabilised following evolution of the primary. The outcome of such instabilities is typically the ejection of one planet, with the survivor being left on an eccentric orbit. These eccentric planets could in turn be responsible for feeding planetesimals into the neighbourhood of White Dwarfs, causing observed pollution and circumstellar discs.